Investigation of Mechanical Properties of Jute Fiber Reinforced Low Density Polyethylene Composites - SANCAK, ERHAN (TAYLOR & FRANCIS INC, 2022)
The environmentally friendly natural fiber reinforced polymers are increasingly taking attention in several industries like automotive and construction due to their properties such as being synthesized in desired properties, easy processing, non-corrosion, low weight, and low cost. In this study, untreated/alkali-treated/silane (1.5%)-treated/alkali+ silane treated jute fabrics (25%) were reinforced to low density polyethylene (LDPE) polymer (75%) with 1%, 3%, 5% and 7% maleic anhydride additives for composite production by using hot pressing method. Further, the effect of jute fabric surface treatments on the tensile strength, flexural strength, and impact resistance properties of the LDPE/jute composites were investigated with the absence/presence of maleic anhydride additives. The results indicate that the alkali/silane treatment of jute fibers led to more than 30% improvement in mechanical properties of the composite structures when reinforced to untreated LDPE, and the mechanical properties of the composites had more than 45% improvement by maleic anhydride addition to the polymer in ideal ratios with untreated jute reinforcement.
Keywords: CHEMICAL TREATMENT; NATURAL FIBER; INTERFACIAL EVALUATION; SURFACE MODIFICATION; TENSILE PROPERTIES; THERMAL-PROPERTIES; POLYPROPYLENE; CELLULOSE; SISAL; PERFORMANCE